1999
DOI: 10.1116/1.590675
|View full text |Cite
|
Sign up to set email alerts
|

Formation and micromachining of Teflon (fluorocarbon polymer) film by a completely dry process using synchrotron radiation

Abstract: Articles you may be interested inSurface micromachining of a thin film microresonator using dry decomposition of a polymer sacrificial layerThe development of a new fabrication technique of Teflon microparts using synchrotron radiation ͑SR͒ irradiation, the SR ablation process, was described. The anisotropic micromachining and thin film formation of polytetrafluoroethylene, fluorinated ethylene propylene, and perfluoroalkoxy were demonstrated using the SR ablation process. The anisotropic micromachining of Tef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 11 publications
1
40
0
Order By: Relevance
“…The higher molecular weight radicals cause a polymer deposition on the top and side wall of contact holes because these radicals have a higher sticking coefficient than the CF 2 radicals in the hole. 18,19 As a result of this, we observed an imbalance between the polymerization and etching, and microloading and etching stop occurred in the high-aspect contact holes. Also, the CF 3 ϩ ion density, the SiO 2 etching rate, and the selectivity were dramatically decreased.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The higher molecular weight radicals cause a polymer deposition on the top and side wall of contact holes because these radicals have a higher sticking coefficient than the CF 2 radicals in the hole. 18,19 As a result of this, we observed an imbalance between the polymerization and etching, and microloading and etching stop occurred in the high-aspect contact holes. Also, the CF 3 ϩ ion density, the SiO 2 etching rate, and the selectivity were dramatically decreased.…”
Section: Resultsmentioning
confidence: 89%
“…However, the polymer deposition rate did not correspond to the CF 2 radical density in the C 4 F 8 /Ar plasma. The other radicals, such as the higher-molecular-weight radicals (C x F y ), 18,19 play a very important role for the polymerization in the C 4 F 8 /Ar plasma. The higher molecular weight radicals cause a polymer deposition on the top and side wall of contact holes because these radicals have a higher sticking coefficient than the CF 2 radicals in the hole.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the direct etching of PTFE sheet was achieved with a high aspect ratio by using synchrotron radiation (SR) Zhang, 1995, 1998;Zhang and Katoh, 1996;Inayoshi et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that direct photo-etching using synchrotron radiation (SR) can be applied in high aspect ratio micromachining of PTFE. 1,2 In these experiments it was found that the photons with energy below 350 eV dominate in the ablation process. Radiation in this range is know as XUV radiation.…”
Section: Introductionmentioning
confidence: 97%